Adult Attachment, Personality and Emotional Intelligence - Fatahyah, Binti Yahya; Eva Ruth, Anak Nohe; Nur Fatihah, Binti Mat Yusoff; Nor Mazlina, Binti Ghazali; Azzahrah, Binti Anuar; Merikan, Bin Aren; Samsiah, Binti Jayos; Mohd Razali, Bin Othman (Hampstead Psychological Associates, 2020)
Children develop different types of emotional bonds to those who care for them. This fact is pertinent here because attachment styles take the form of disparate, relatively stable patterns of emotionality that influences relationships, reaction to stress or loss and other emotional dilemmas in life. Different attachment styles create different personality for an adult. Due to this reason, recognizing our attachment pattern can help us understand our strengths and weaknesses of our personality. This study aims to identify the relationship between adult attachment, personality and emotional intelligence among trainee counsellors in Universiti Malaysia Sarawak (UNIMAS). This research adopted a correlational research design. The sample consists of 106 respondents from year 3 and year 4 trainee counsellors in Universiti Malaysia Sarawak. The study consists of three main variables which are attachment dimension, Big Five Personality and emotional intelligence. In this study, the questionnaires used were Experience in Close Relationship (ECR), Big Five Personality and The Schutte Self Report Emotional Intelligence Test (SSEIT). The finding indicated that there is a significant relationship between adult attachment; anxiety and personality; agreeableness and neuroticism. The outcome of the study would be an essential finding that would raise awareness on the importance of adult attachment, personality and emotional intelligence. Knowing our attachment dimension, personality traits as well as emotional intelligence would help us develop a working plan to cope with our environment.